SILABUS EAP BERBASIS LEARNING OUTCOMES UNTUK MAHASISWA IAIN SURAKARTA - Imroatus Solikhah (Center of Language and Cultural Studies, 2017)
The objectives of this study are: (1) to describe conditions of MKDU Bahasa Inggris at IAIN Surakarta, (2) to formulate needs analysis of Learning Outcomes-Based EAP program at IAIN Surakarta, and (3) to develop a syllabus of Learning Outcomes-Based EAP Program at at IAIN Surakarta. The design of this study is R2D2 (Recursive, Reflective, Design and Development) that used three phases: define, design and develop, and disseminate and assigned 3 language experts, 6 English lecturers, and 20 students as research subjects. This study finds two findings. First, conditions of MKDU Bahasa Inggris program at IAIN Surakarta are not standard. MKDU Bahasa Inggris is general English and syllabus is not available. Second, Learning Outcomes EAP Syllabus should be used to achieve academic literacy and minimum English competency. The core materials include: reading for literal, inferential, and critical; speaking for informal, formal, and academic setting; general word list 1,000 to 2,000, academic vocabulary, basic grammar, and academic grammar.